Síntese, caracterização e estudo fotofísico de novas calcogenoporfirinas derivadas da 5,10,15,20–tetrakis (4-bromometilfenil)porfirina - Garcia, Fábio Dutra (2020)
In this work, two classes of porphyrins were prepared, the first involving the synthesis of new calcogenoporphyrins derived from 5,10,15,20 - tetrakis (4-bromomethylphenyl) porphyrin, characterization and study of photophysical properties, and the second, the synthesis of new metalloporphyrins from previous thioaryl porphyrins, characterization and study of photophysical properties. For the first class of compounds, a synthetic route that synthesizes the synthesis of four compounds derived from 5,10,15,20 - tetrakis (4-bromomethylphenyl) porphyrin is specialized. Tetrasubstituted calcogenporphyrins derived from 5,10,15,20 - tetrakis (4-bromomethylphenyl) porphyrin were used using p-methyl-diphenyl-diselenide, p-chloro-diphenyl-diselenide, diphenyl-diselenide and diphenyl-disulfide as a source of anion of arylcalcogen. Thus, the synthesis of calcogenoporphyrins occurred through a second order nucleophilic substitution reaction between 5,10,15,20 - tetrakis (4-bromomethylphenyl) porphyrin and a nucleophile derived from aryl-dicalcogen. The formation of the products depends on the control of the reaction time, and the amount of sodium borohydride. Thus a series of 4 new molecules of chalcogenpyrphyrins were displaced. In the synthetic route applied, the formation of products in good settings (58-65%) stands out, in a short reaction time, without the use of base in the reaction medium and with the use of reagents that are easy to handle. The compounds were characterized by ¹H and 77Se nuclear magnetic resonance (NMR), high resolution mass spectrometry (HRMS-ESI (+)), electronic spectroscopy in the ultraviolet-visible (UV-vis) regions and fluorescent emission spectroscopy. In addition, quantum conformation studies of fluorescence and singlet oxygen generation (ΦΔ) were carried out. In addition, a second class of porphyrins was prepared, in all a series of 16 metalloporphyrins derived from zinc, copper, nickel and cobalt were synthesized from thioaryl porphyrins previously prepared. Through methodologies already outdated in the literature and with specific optimizations, all 16 metalloporphyrins were shipped with more than 95% yield. These new compounds were characterized by ¹H NMR and UV-Vis absorption and fluorescence emission spectroscopies. Metalloporphyrins with zinc present much higher values of quantum fluorescence supplements, when compared to the TPP standard, being up to 3 times higher for two examples. For the other metalloporphyrins, although presented fluorescence emission, the good quantum ones were much lower than the TPP standard.